2021
DOI: 10.33084/jsm.v7i1.2651
|View full text |Cite
|
Sign up to set email alerts
|

Optimasi Kombinasi Asam Sitrat dan Asam Tartrat sebagai Zat Pengasam pada Tablet Effervescent Ekstrak Ubi Jalar Ungu (Ipomoea batatas L)

Abstract: Purple sweet potato has the content of anthocyanin compounds that are efficacious as antioxidants. To deliver these efficacious compounds, formulations of effervescent tablets are required as antioxidants with a combination of citric acid and tartrate acid to accelerate the solubility of the drug. The research aims to optimize the combination of citric acid and tartrate acid as a sourgent on effervescent tablets of purple sweet potato extract using the simplex lattice design method. The manufacture of tablets … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0
9

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(13 citation statements)
references
References 5 publications
0
4
0
9
Order By: Relevance
“…The bottom cover of the funnel was opened and the fall time of the granules was calculated using a stopwatch (20). The flow rate is said to be good if it has a flow rate of less than 10 g/sec (21).…”
Section: Flow Ratementioning
confidence: 99%
See 1 more Smart Citation
“…The bottom cover of the funnel was opened and the fall time of the granules was calculated using a stopwatch (20). The flow rate is said to be good if it has a flow rate of less than 10 g/sec (21).…”
Section: Flow Ratementioning
confidence: 99%
“…The granules flow rate test aims to determine the quality of the effervescent granules because, in the tablet printing process, the flow rate of the powder/granules is greatly affected by the flow rate test (29). The flow rate is said to be good if it has a flow rate of not less than 10 g/sec (21). The results of the flow rate test showed that formula 1 had a better granule flow rate than formulas 2 and 3 (see Figure 2).…”
Section: Flow Rate Of Effervescent Granulesmentioning
confidence: 99%
“…Namun F3 yang paling baik karena nilainya lebih kecil. Hal ini sejalan dengan penelitian (Syahrina & Noval, 2021) optimasi kombinasi asam sitrat dan asam tartrat sebagai zat pengasam pada tablet effervescent ekstrak ubi jalar ungu (Ipomoea batatas L) diperoleh kadar air sebesar 1-5%.…”
unclassified
“…Hasil pengujian berdasarkan tabel 3 ketiga formula memenuhi persyaratan kurang dari 10 detik. Hal ini sejalan dengan penelitian (Syahrina & Noval, 2021) optimasi kombinasi asam sitrat dan asam tartrat sebagai zat pengasam pada tablet effervescent ekstrak ubi jalar ungu (Ipomoea batatas L) diperoleh waktu alir dalam rentang 3-5 detik.…”
unclassified
See 1 more Smart Citation